Acute eosinophilic pneumonia associated with glyphosate-surfactant exposure - de Raadt, Wanda M.; Wijnen, Petal A.; Bast, Aalt; Bekers, Otto; Drent, Marjolein (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
We report a case of a female patient who developed acute eosinophilic pneumonia (AEP) after recent onset of smoking and exposure to glyphosate-surfactant. The additional exposure associated with the recent start of smoking may have contributed to the development and/or severity of AEP. A clinical relapse after re-challenge four years later both with smoking and glyphosate-surfactant made the association highly likely. Respiratory distress is a factor of poor outcome and mortality after ingestion of glyphosate-surfactant. This case highlights the importance of a thorough exposure history e.g., possible occupational and environmental exposures together with drug-intake. Genotyping should be considered in cases of severe unexplained pulmonary damage